Strain measurement based on cooperative operation with different smartphones. (16th September 2022) - Xie, Botao; Zhang, Lixiao; Ding, Mingwei; Li, Weijie; Zhao, Xuefeng
Abstract: Strain measurement is one of the critical procedures in detecting failures and health monitoring for various structures in the field of civil engineering. This article demonstrates a smartphone‐based cooperative strain measurement method called micro image strain sensing (MISS) for widespread and low‐cost structural strain monitoring. The method relies on smartphones, the piston‐type sensor with a microscope fitted on it, and the Android platform with cloud computing. The detailed principle of the MISS method and fabrication of the MISS sensor and the comparison of measurement accuracy with fiber Bragg grating sensor are presented. The results show that the error is within 10 με., which satisfies the engineering requirement, and the sensor exhibits high flexibility, high reliability, and high linearity. The work highlights the potential of widespread usage and public participation in smartphone‐based strain measurement for the structural health monitoring of the next generation.